A conductive polymer composite derived from polyurethane and cathodically exfoliated graphene. (January 2023) - Dalal, M.H.; Sayyar, S.; Lee, C.-Y.; Wallace, G.G.
Abstract: Composite electrodes represent an important class of electromaterials, with enhanced functional properties tailored for targeted applications. Introduction of graphene as a conductive nanofiller into the thermoplastic polyurethane (PU) provides electrodes with interesting properties. In this study, a highly conductive cathodically exfoliated graphene (CEG) of ∼2–8 μm lateral size was employed to prepare CEG-PU composites. The use of this larger graphene sheet requires loading of at least 20% w/w graphene to promote contact between the sheets, hence the conductivity. The CEG-PU composite electrodes were tested to determine their electrochemical capacitance and it was found that the 40% (w/w) CEG-PU composite shows areal capacitance, energy density, and power density of 2.51 mF/cm 2, 1.56 μW/h/cm 2, and 0.48 mW/cm 2, respectively, at a current density of 0.2 mA/cm 2 and an operating voltage of 1.0 V. In summary, the CEG-PU composite electrodes have excellent conductivity, chemical/mechanical properties, and capacitive performance. Highlights: A highly conductive cathodically exfoliated graphene was employed to synthesis graphene–polyurethane composites. Higher loading of large graphene sheets are needed for the composites to be electrically conductive. Composite contained 40% (w/w) graphene showed the best electrochemical capacitance performance.